2011
DOI: 10.2334/josnusd.53.467
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of Fcγ-receptors IIa, IIIa and IIIb in South Indian patients with generalized aggressive periodontitis

Abstract: Recent evidence suggests that polymorphisms in Fcγ receptors are associated with different forms of periodontitis. However, the FcγR genotypes and their allele frequency differ among subjects from different ethnic backgrounds. The aim of the present study was to determine whether specific FcγRIIa, FcγRIIIa, and FcγRIIIb alleles and/or genotypes are associated with susceptibility to generalized aggressive periodontitits (GAgP) in a South Indian population. Buccal scrapings were obtained from 60 subjects with GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
12
1
Order By: Relevance
“…However, stratification by ethnicity revealed an association between the RR+RH genotype with periodontitis in a white population, but not in East Asian and African populations 36 . A recent study in patients with AgP from an ethnically similar population in South India reported a higher prevalence of the R allele in patients with AgP 10 . The present study has demonstrated a lack of association of FCGR2A His/Arg SNP with CP susceptibility in the 25‐ to 50‐year age cohort from South India.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, stratification by ethnicity revealed an association between the RR+RH genotype with periodontitis in a white population, but not in East Asian and African populations 36 . A recent study in patients with AgP from an ethnically similar population in South India reported a higher prevalence of the R allele in patients with AgP 10 . The present study has demonstrated a lack of association of FCGR2A His/Arg SNP with CP susceptibility in the 25‐ to 50‐year age cohort from South India.…”
Section: Discussionmentioning
confidence: 92%
“…Candidate gene studies evaluating association of the SNP in the FcGR gene complex with chronic periodontitis (CP) susceptibility have given inconclusive results 7–9 . Published literature on the role of SNP in FCGR2A , 2B , 3A , 3B and CP susceptibility in the Indian population is scant 10 …”
mentioning
confidence: 99%
“…For example, the FcγRIIa-H131 genotype was found to be associated with an increased production of the pro-inflammatory cytokine IL-1β by mononuclear cells, leading to inter-individual differences in the risk for acquiring periodontitis [140]. In multiple studies carried out in diverse ethnic populations, significant associations were found between FcγR polymorphisms and inter-individual differences in susceptibility, prevalence, and prognosis of diseases like systemic lupus erythematosus (SLE) [141][142][143][144], rheumatoid arthritis (RA) [145,146], immune thrombocytopenia [147], Guillain-Barré syndrome [148][149][150], myasthenia gravis [151] pediatric autoimmune neutropenia [152], IgA nephropathy [153], inflammatory myopathies [154], anti-glomerular basement membrane antibody disease [155], Kawasaki Disease [156], periodontitis [157,158], malaria [159,160], dengue [161], and sickle cell disease [162].…”
Section: Fc Gamma Receptor Expression and Polymorphismmentioning
confidence: 99%
“…Although, NA1/NA2 polymorphism has been linked with GAgP, the studies on its association with GCP are limited. [ 18 ] Except for one study where FcγRIIIbNA2/NA2 was more prevalent in GCP patients,[ 30 ] none of the studies have found a relationship between this genotype and chronic periodontitis. [ 35 36 ] Our results also did not show any significant difference in the distribution of FcγRIIIb genotypes between GCP and controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study on genetic polymorphism of FcγRIIa, IIIa, and IIIb genes in South Indian population with generalized aggressive periodontitis (GAgP), it was concluded that FcγRIIIa V/V genotypes and/or V allele as well as FcγRIIIb NA2/NA2 and/or NA2 allele along with FcγRIIa R allele may be a risk factor for GAgP. [ 18 ]…”
Section: Introductionmentioning
confidence: 99%